2017
DOI: 10.1111/mmi.13838
|View full text |Cite
|
Sign up to set email alerts
|

The role of genomic location and flanking 3′UTR in the generation of functional levels of variant surface glycoprotein in Trypanosoma brucei

Abstract: Summary Trypanosoma brucei faces relentless immune attack in the mammalian bloodstream, where it is protected by an essential coat of Variant Surface Glycoprotein (VSG) comprising ∼10% total protein. The active VSG gene is in a Pol I‐transcribed telomeric expression site (ES). We investigated factors mediating these extremely high levels of VSG expression by inserting ectopic VSG117 into VSG221 expressing T. brucei. Mutational analysis of the ectopic VSG 3′UTR demonstrated the essentiality of a conserved 16‐me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 86 publications
2
47
0
Order By: Relevance
“…Under iron starvation conditions the repressive effect of the ESAG6 3’UTR is reduced, resulting in an increase of expression that is most likely driven by an increase in transcript abundance, as Tb TfR increases equally at the mRNA and protein level (9, 10). The involvement of the 3’UTR in iron starvation response suggest that it contains secondary structural elements or sequence motifs that are recognised by RNA binding protein(s) (RBPs), but the high level of sequence conservation in the UTR makes it likely that any such features are more extensive than the 16-mer regulatory sequence identified in VSG mRNAs (28). Further experiments will be required to identify any regulatory features present in the ESAG6 3’-UTR, and whether they have a positive or negative regulatory role.…”
Section: Discussionmentioning
confidence: 99%
“…Under iron starvation conditions the repressive effect of the ESAG6 3’UTR is reduced, resulting in an increase of expression that is most likely driven by an increase in transcript abundance, as Tb TfR increases equally at the mRNA and protein level (9, 10). The involvement of the 3’UTR in iron starvation response suggest that it contains secondary structural elements or sequence motifs that are recognised by RNA binding protein(s) (RBPs), but the high level of sequence conservation in the UTR makes it likely that any such features are more extensive than the 16-mer regulatory sequence identified in VSG mRNAs (28). Further experiments will be required to identify any regulatory features present in the ESAG6 3’-UTR, and whether they have a positive or negative regulatory role.…”
Section: Discussionmentioning
confidence: 99%
“…CFB2 depends on a conserved 16mer in the 3'-UTR Supplementary Fig 10). Experiments using reporter mRNAs have shown that the 16-mer is required for high mRNA abundance and stability in bloodstream forms (12,13). It is also required for m 6 A modification of the poly(A) tail, which plays a role in VSG mRNA stabilization (67).…”
Section: Graph Showing Effects Of Tethering Different Versions Of mentioning
confidence: 99%
“…The 16mer sequence is required to maintain the ~2h VSG half-life in bloodstream forms (11)(12)(13). After uptake into the tsetse fly vector, the trypanosomes convert to the procyclic form; VSG transcription is shut off, the mRNA becomes unstable (11,12) and the VSG coat is lost.…”
Section: Introductionmentioning
confidence: 99%
“…Another mechanism for elevating VSG production involves post‐transcriptional regulation. VSG mRNAs are exceptionally stable ( t 1/2 ≈2 h), a phenomenon mediated by a conserved 14‐mer in the 3′ UTR . Mutation of the 14‐mer reduces stability (≈5.5‐fold) to levels equivalent to most other mRNAs.…”
Section: Just Right: How Do Trypanosomes Precisely Regulate Vsg Synthmentioning
confidence: 99%